Influence of geometric configurations of recycled plastic micropiles on the safety factor of coastal slopes: Case study of the slope adjacent to the Manuel Bonilla-Peru port complex. - Velita, Sadit Acuna (2023)
This scientific article presents a comprehensive analysis of geometric configurations of recycled plastic micropiles for slope stabilization in challenging coastal environments. The study focuses on the Miraflores slope in the Costa Verde area of Lima, Peru. The research includes a detailed investigation of the soil's geotechnical properties and slope conditions, followed by the design of different geometric configurations of recycled plastic micropiles. These configurations undergo numerical analysis using the PLAXIS 2D software to evaluate the slope stability under various scenarios. The obtained results, this study contributes to the advancement of knowledge in the field of civil engineering and provides specific and applicable data that can have a direct impact on engineering projects in similar geographical areas, promoting informed decision-making and a more sustainable approach in engineering practice.